Accumulation of heavy metals in crop plants through irrigation of contaminated ground water in Panipat region - D. S. Malik; Rashmi Yadav; Pawan K. Bharti (Environment Conservation Journal, 2004)
In the modern industrialization period, most of water resources had affected enormously by seepage, leaching and intermixing of industrial effluents. The textile effluents had consisting high concentrations of trace heavy metals and through its accumulations in different trophic levels of ecosystem ultimately cause the health hazards among livestock and human beings. The different crop plant samples collected from agriculture fields adjoining of textile industrial effluent  flowing channels contained in situ these heavy metals e.g. Lead (pb), Copper (Cu), Manganese (Mn), Nickel (Ni), Iron (Fe), Cadmium (Cd) and Zinc (Zn). The bioremediation processes are urgently required to combat ground water pollution.